The Influence of Leadership, Motivation and Work Discipline on Teacher Performance With Job Satisfaction As An Intervening Variable in Arifah Madrasah - Ulfa Tiara, Qanita; Badawi Saluy, Ahmad; Bari, Abdul (International Journal of Advanced Multidisciplinary, 2023)
This study investigates the influence of leadership, motivation and work discipline on teacher performance through job satisfaction at madrasah arifah. This research uses a quantitative approach through questionnaires to 98 respondents with a Likert scale with analysis using SEM-PLS (Structural Equation Modeling-Partial Least Square). The research results show:leadership has a positive and significant effect on teacher performance, motivation has a positive and significant effect on teacher performance, work discipline has a positive and significant effect on teacher performance, job satisfaction has a positive and significant effect on teacher performance, leadership has a positive and significant effect on job satisfaction, motivation has a positive effect and significant to teacher job satisfaction, work discipline has a positive and significant effect on teacher job satisfaction, leadership has an indirect effect on teacher performance, motivation has an indirect effect on teacher performance, work discipline has an indirect effect on teacher performance, so it can be concluded that leadership, motivation , and work discipline has a positive and significant effect on teacher job satisfaction at Arifah Madrasah.